Հույն (Բյուզանդական) ուղղափառ եկեղեցու հետևորդ համայնքը Կիլիկիայում ԺԳ-ԺԴ դդ. կեսերին - Ավետիսյան, Վահե (Մատենադարան)
Until the end of the 12th century, negotiations between the Armenian clergy of Cilicia and the Byzantine Church were periodically held on the restoration of church communion, which, unfortunately, did not lead to positive results. After the coronation of Levon II in 1198, Cilician Armenia formally recognized the primacy of the Roman Church. This circumstance did not affect the rights of the Greek-Orthodox population of the country: the community retained its dioceses throughout the kingdom and even managed to strengthen its position after the Hethumids came to power. Following the conquest of Antioch in 1268, the Greek-Orthodox population of Cilicia united even more, taking an active place in the former territories of the Patriarchate of Antioch. It was a small but relatively influential part of the population of the kingdom, represented in all spheres of life, and only from the 40s of the 14th century, when the state was declining, the Orthodox community began to disperse quickly. Вплоть до конца XII в. между армянским духовенством Киликии и Византийской церковью периодически шли переговоры о восстановлении церковного общения, которые не привели к положительным результатам. После коронации Левона II в 1198 г. Киликийская Армения формально приняла главенство Римской церкви. Данное обстоятельство, однако, не привело к притеснениям греко-православного населения страны: община сохранила свои епархии по всему королевству и даже сумела укрепить свои позиции после прихода к власти Хетумидов. После завоевания Антиохии в 1268 г., греко-православное население Киликии ещё больше сплотилось, и стало играть еще более активную роль на бывших территориях Антиохийского патриархата. Оно по-прежнему оставалось значительной частью населения королевства, было представлено во всех областях жизни и только с 40-х гг. XIV в., на фоне упадка государства, православная община быстро рассеивается.
Keywords: Հույն Ուղղափառ եկեղեցի